Structural characteristics of the bone surrounding dental implants placed into the tail-suspended mice - Yuto Otsu; Satoru Matsunaga; Takehiro Furukawa; Kei Kitamura; Masaaki Kasahara; Shinichi Abe; Takayoshi Nakano; Takuya Ishimoto; Yasutomo Yajima (SpringerOpen, 2021)
Abstract Background There are many unclear points regarding local structural characteristics of the bone surrounding the implant reflecting the mechanical environment. Purpose The purpose of this study is to quantitatively evaluate bone quality surrounding implants placed into the femurs of mice in an unloading model, and to determine the influence of the mechanical environment on bone quality. Methods Twenty 12-week-old male C57BL6/NcL mice (n = 5/group) were used as experimental animals. The mice were divided into two groups: the experimental group (n = 10) which were reared by tail suspension, and the control group (n = 10) which were reared normally. An implant was placed into the femur of a tail-suspended mouse, and after the healing period, they were sacrificed and the femur was removed. After micro-CT imaging, Villanueva osteochrome bone stain was performed. It was embedded in unsaturated polyester resin. The polymerized block was sliced passing through the center of the implant body. Next, 100-μm-thick polished specimens were prepared with water-resistant abrasive paper. In addition to histological observation, morphometric evaluation of cancellous bone was performed, and the anisotropy of collagen fibers and biological apatite (BAp) crystals was analyzed. Results As a result, the femoral cortical bone thickness and new peri-implant bone mass showed low values in the tail suspension group. The uniaxial preferential orientation of BAp c-axis in the femoral long axis direction in the non-implant groups, but biaxial preferential orientation of BAp c-axis along the long axis of implant and femoral long axis direction were confirmed in new bone reconstructed by implant placement. Collagen fiber running anisotropy and orientation of BAp c-axis in the bone surrounding the implant were not significantly different due to tail suspension. Conclusions From the above results, it was clarified that bone formation occurs surrounding the implant even under extremely low load conditions, and bone microstructure and bone quality adapted to the new mechanical environment are acquired.